Itaconate family-based host-directed therapeutics for infections - Yuk, Jae-Min; Park, Eun-Jin; Kim, In Soo; Jo, Eun-Kyeong (Frontiers in Immunology, 2023)
Itaconate is a crucial anti-infective and anti-inflammatory immunometabolite that accumulates upon disruption of the Krebs cycle in effector macrophages undergoing inflammatory stress. Esterified derivatives of itaconate (4-octyl itaconate and dimethyl itaconate) and its isomers (mesaconate and citraconate) are promising candidate drugs for inflammation and infection. Several itaconate family members participate in host defense, immune and metabolic modulation, and amelioration of infection, although opposite effects have also been reported. Here we review how the immune response gene 1-itaconate pathway is activated during infection and its role in host defense and pathogenesis in a context-dependent manner. Certain pathogens can use itaconate to establish infections. Finally, we briefly discuss the major mechanisms by which itaconate family members exert antimicrobial effects.